Policy Implementation of Teacher Competence in Practicing Islamic Teaching - Acep Heris Hermawan; Maemunah Sa'diyah; Hary Priatna Sanusi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2017)
This study aimed to find out the implementation of teacher competence, the practice of Islamic teaching, supporting and inhibiting factors of the implementation of teacher competence policy. The research used qualitative approach, and was conducted at MAN (Madrasah Aliyah Negeri/Islamic Senior High School) 1 Bandung, MAN Cipasung Tasikmalaya, and MAN Ciwaringin Cirebon. The data were collected through observations, interviews, documents, and questionnaires. The study found that the implementation of a policy in Islamic schools model had been running effectively. The teachers’ competence had complied professionalism standard. The practice of Islamic teaching had described the dimension of religious practices dynamically and systematically. The supporting factors consisted of a qualified manpower, adequate structures and infrastructures, the atmospheres of excellent academic and spirituality, and the support from all elements of madrasa. The implication of the policy implementation of teacher competence in cultivating the practice of religious teaching in madrasas contributed to the improvement of madrasa quality, teacher competence and performance, and students’ good deed and achievement.